2017
DOI: 10.1128/jvi.00401-17
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of a CD4-Mimetic Miniprotein with HIV-1 Env gp140 Alters Kinetics and Specificities of Antibody Responses against HIV-1 Env in Macaques

Abstract: Evaluation of the epitope specificities, locations (systemic or mucosal), and effector functions of antibodies elicited by novel HIV-1 immunogens engineered to improve exposure of specific epitopes is critical for HIV-1 vaccine development. Utilizing an array of humoral assays, we evaluated the magnitudes, epitope specificities, avidities, and functions of systemic and mucosal immune responses elicited by a vaccine regimen containing Env cross-linked to a CD4-mimetic miniprotein (gp140-M64U1) in rhesus macaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Importantly, we observed neutralizing responses against HIV-2 (Y720S) in the presence of sCD4 in the CD4-bound gp140 group, confirming that the CD4i epitopes were exposed, functional, and induced by this immunogen ( Fig. 7 ), and this was independently confirmed by Shen et al ( 27 ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, we observed neutralizing responses against HIV-2 (Y720S) in the presence of sCD4 in the CD4-bound gp140 group, confirming that the CD4i epitopes were exposed, functional, and induced by this immunogen ( Fig. 7 ), and this was independently confirmed by Shen et al ( 27 ).…”
Section: Resultssupporting
confidence: 86%
“…6 ). Given that globally the Env-neutralizing epitopes were otherwise identical in the CD4bs-blocked versus CD4bs-open gp140, this was not unexpected (with the exception of fine specificity differences of CD4i epitopes caused by CD4bs-M48U1 cross-linking [ 27 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of viral neutralizing antibodies (nAbs), studies have shown that both monomeric gp120 and trimeric gp140 HIV-1 vaccines induce neutralizing antibody responses but still lack sufficient breadth to effectively protect against diverse HIV-1 isolates (García-Arriaza et al, 2017; Shen et al, 2017). HSV-2 gB or gD subunit vaccines could induce high levels of neutralizing Abs but could not efficiently protect mice against a viral challenge (Zhu et al, 2014).…”
Section: Ccl19 As a Molecular Adjuvant Enhances Virus-specific Immunementioning
confidence: 99%
“…Crosslinking of HIV-1 Env amino acid residues, in some cases combined with mass spectrometry, has been used to study Env conformations (37,73,(126)(127)(128)(129)(130)(131).…”
Section: Introductionmentioning
confidence: 99%